Insulin sensitizer in prediabetes: a clinical study with DLBS3233, a combined bioactive fraction of Cinnamomum burmanii and Lagerstroemia speciosa - Manaf A; Tjandrawinata RR; Malinda D (Dove Medical Press, 2016)
Asman Manaf,1 Raymond R Tjandrawinata,2 Desi Malinda1 1Department of Internal Medicine, Faculty of Medicine, University of Andalas, Dr M Djamil Padang Hospital, Padang, 2Dexa Laboratories of Biomolecular Sciences (DLBS), Cikarang, Indonesia Background: The aim of this paper is to evaluate the efficacy and safety of DLBS3233, a novel bioactive fraction derived from Cinnamomum burmanii and Lagerstroemia speciosa, in improving insulin resistance and preserving β-cell performance in patients with impaired glucose tolerance (IGT).Patients and methods: Eighty adult subjects with IGT, defined as 2-hour postprandial glucose level of 140–199 mg/dL, were enrolled in this two-arm, 12-week, double-blind, randomized, placebo-controlled preliminary study. Eligible subjects were randomly allocated to receive either DLBS3233 at a dose of 50–100 mg daily or placebo for 12 weeks. The study mainly assessed the improvement of homeostatic model-assessed insulin resistance (HOMA-IR), the 15-minute and 2-hour plasma insulin levels, and the oral disposition index.Results: After 12 weeks, DLBS3233 improved insulin resistance better than placebo as reflected by a reduced HOMA-IR (-27.04%±29.41% vs -4.90%±41.27%, P=0.013). The improvement of the first- and second-phase insulin secretion was consistently greater in DLBS3233 group than placebo group (-144.78±194.06 vs -71.21±157.19, P=0.022, and -455.03±487.56 vs -269.49±467.77, P=0.033, respectively). Further, DLBS3233 also significantly better improved oral disposition index than placebo. No serious hypoglycemia, edema, or cardiovascular-related adverse events were found in either groups.Conclusion: This study has shown that DLBS3233 at the dose of 50–100 mg once daily was well tolerated, and promisingly efficacious in improving insulin sensitivity as well as preserving β-cell performance in subjects with IGT. Keywords: β-cell function, Cinnamomum burmanii, DLBS3233, Lagerstroemia speciosa, impaired glucose tolerance, insulin resistance